2022
DOI: 10.1136/bmjopen-2021-049225
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessing metabolic abnormalities, lifestyle and dietary pattern in a Chinese population with heart failure: the MALD-HF study protocol

Abstract: IntroductionThe evidence on predictive value of lifestyle behaviours and dietary pattern on the prognosis of heart failure (HF) is limited. Our aim is to identify these factors in the setting of secondary prevention of HF.Methods and analysisThe Metabolic Abnormalities, Lifestyle and Dietary Pattern in Heart Failure study is an ongoing, prospective cohort, single-centre study that aims to recruit 1500 patients with HF from June 2016 to June 2021. At baseline, each participant completes a questionnaire on demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…A healthy lifestyle, regular diet and exercise habits, and good medication habits all have a significant impact on the prognosis of heart failure patients. 12,50,51 The results of this meta-analysis showed that mHealth interventions could effectively reduce the mortality of patients with heart failure. The decrease in mortality in the intervention group was 0.63% higher than that in the control group.…”
Section: Influence On Mortalitymentioning
confidence: 88%
“…A healthy lifestyle, regular diet and exercise habits, and good medication habits all have a significant impact on the prognosis of heart failure patients. 12,50,51 The results of this meta-analysis showed that mHealth interventions could effectively reduce the mortality of patients with heart failure. The decrease in mortality in the intervention group was 0.63% higher than that in the control group.…”
Section: Influence On Mortalitymentioning
confidence: 88%